Reducing Sugar Production from Teff Straw Biomass Using Dilute Sulfuric Acid Hydrolysis: Characterization and Optimization Using Response Surface Methodology - Andinet Alemayehu Tesfaw; Belachew Zegale Tizazu (International Journal of Biomaterials)
The present study evaluated first the characterization of Teff straw and then Box–Behnken design (BBD), and response surface methodology was adopted to optimize the parameters (hydrolysis temperature, dilute sulfuric acid concentration, solid to liquid ratio, and hydrolysis time) of dilute sulfuric acid hydrolysis of Teff straw in order to get a maximum yield of total reducing sugar (TRS). The chemical analysis of Teff straw revealed high amounts of cellulose (41.8 wt%), hemicellulose (38 wt%), and lignin (17 wt%). The morphological analysis using SEM showed that hydrolyzed Teff straw with dilute sulfuric acid has more pores and distorted bundles than those of raw Teff straw. XRD analysis also indicated that hydrolyzed Teff straw has higher crystallinity index and smaller crystallite size than raw Teff straw, which might be due to removal of hemicellulose, amorphous cellulose, and lignin components. Under the optimized conditions for dilute sulfuric acid hydrolysis of Teff straw (120°C, 4% v/v H2SO4 concentration, 1 : 20 solid to liquid ratio, and 55 min hydrolysis time), we have found a total reducing sugar yield of 26.65 mg/g. The results of validation experiment under the optimum conditions agreed well with model predictions.